English Instructional Materials: Imperative Learning Aid for the High School Bound Summer Program of the MSU-Science High School - Tan , Jose G. (International Journal of Learning, Teaching and Educational Research, 2016)
This study was conducted to meet the long-felt need of the MSU-Institute of Science EducationScience High School to have English instructional materials that will be used for its High School Bound Summer Program. The descriptive method of research and a quantitative analysis of the performance of the respondents on the Proficiency Test were used in this study. The inquiry started off with a needs analysis through a proficiency test administered to the Grade VI pupils of MSU-Integrated Laboratory School (ILS), Ibn Sienna Integrated School, Foundation (ISISF) and Ranao Child Development Center (RCDC). A modified proficiency test was used in this study. To establish reliability and validity, it was patterned after the English Language Proficiency Test (ELPT) of the Language Center of MSU-College of Social Sciences and Humanities. The proficiency test consisted of three parts: Test of Language Use (TLU), Test of Written English (TWE) and Test of Spoken English (TSE). Each respondent was given an answer sheet for Parts I and II. By means of stratified random sampling, a smaller number of respondents drawn from the original sample of 263 respondents were selected to take Part III which was in the form of an interview. Their answers were tape recorded and then evaluated and rated by three (3) competent faculty members. The needs analysis yielded the following findings: majority of the respondents of the three elementary schools have a minimum knowledge about the structure of English language such as sentences, clauses, vocabulary and reading comprehension; majority of the respondents have attained only low proficiency levels in writing; and majority of the respondents displayed hesitations and difficulty in listening and speaking. In short, there is a serious problem in English language proficiency of the respondents in terms of writing, listening and speaking. Based on the overall result, majority of respondents could be said to be suffering from what is known as Limited English Proficiency (LEP) and are likely at risk for learning disabilities or failure. Although no single cause could be pin-pointed, it can be hypothesized that impoverished background and inadequate training are contributory factors. The problem can be remedied by addressing the students’ weaknesses. Materials can be designed for this purpose. Hence, better performance in English language proficiency is possible if lessons and activities address the needs of the pupils.